Escape from New York [videorecording (DVD)] - Carpenter, John, 1948-; Carpenter, John, 1948-; Russell, Kurt; Van Cleef, Lee, 1925-1989; Borgnine, Ernest, 1917-2012; Pleasence, Donald; Barbeau, Adrienne, 1945- (MGM DVD., 2003)
In a world ravaged by crime, the entire island of Manhattan has been converted into a prison which houses the world's most brutal inmates. And when the President of the United States crash lands inside, only one man can bring him back: Snake Plissken, a notorious outlaw and former Special Forces war hero who, in exchange for a full pardon, descends into the decayed city and wages a blistering war against the captors. But time is short: in 24 hours, an explosive charge planted inside Snake's body will end the mission-- and his life-- unless he succeeds!